The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1021/ic00065a013
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of (.eta.7-cycloheptatrienyl)(.eta.5-cyclopentadienyl)M (M = titanium, niobium) toward dithioacetic acid: preparation and characterization of (.eta.5-C5H5)Ti(S2CCH3)3 and (.eta.5-C5H5)Nb(.eta.2-S2)(S2CCH3)2

Abstract: A method for the high-yield syntheses (up to 85%) of the two new compounds (j75-C5H5)Tí(S2CCH3)3 ( 1) and ( 7)5-C5Hs)Nb(jj* 12-S2)(S2CCH3)2 ( 2) from (n7-C7H7)M(»j5-C5H5) (M = Ti, Nb) and dithioacetic acid, CH3CS2H, is described. Both compounds are characterized by elemental analysis, and 13C NMR spectroscopy, infrared spectroscopy, mass spectrometry, and X-ray crystallography. Compound 1 crystallizes in orthorhombic space group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…identical, and are comparable to the average Ti-S distances reported for the Ti() species Ti(S 2 CNEt 2 ) 4 (2.564 Å),9 CpTi(S 2 CMe) 3 (2.603 Å),10 and CpTi(S 2 CNMe 2 ) 3 (2.611 Å) 11. Although[2,6-…”
supporting
confidence: 81%
“…identical, and are comparable to the average Ti-S distances reported for the Ti() species Ti(S 2 CNEt 2 ) 4 (2.564 Å),9 CpTi(S 2 CMe) 3 (2.603 Å),10 and CpTi(S 2 CNMe 2 ) 3 (2.611 Å) 11. Although[2,6-…”
supporting
confidence: 81%
“…As a result, these weakly interacting electrons in the d xy orbitals on each vanadium center give rise to the EPR signal. [12] and Ta-complexes [(Cp*Ta) 2 (μ-S){μ-C(H)S 3 -k 2 S : k 1 S',S''}{μ-SC(H)S-k 2 C : k 1 S''',S''''}] [14] and [(Cp*Ta) 2 (μ-S)(μ-S 2 CH 2 CHS 2 -k 2 S : k 1 S',S'')(μ-H)(μ-S 2 CH 2 k 1 S''',S'''')]. [17] On the other hand, the four equatorial sulfur atoms of 4 a and 4 b are not located in the same plane which is reflected in the average S eq À MÀ S eq bond angles (4 a: 86. planar geometry (90°).…”
Section: Reactivity Of [Cp*vcl 2 ] 3 (1) With [Hs(ch 2 ) 2 Sh]mentioning
confidence: 99%
“…In 1993, Duraj group reported the first group 4 thiolato complex [CpTi(S 2 CCH 3 ) 3 ] (D) having dithioacetate ligands. [12] This complex is an example of seven-coordinated distorted pentagonal bipyramidal species, in which the Ti atom coordinated to six sulfur atoms and one Cp ligand. In 1990, Tatsumi synthesized various bis-and tris-chelated dithiolato Nb(IV) and Ta(V) and tetrakis(arenethiolato) complexes of divalent transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…218 Treatment of (η 7 -C 7 H 7 )Ti(η 5 -C 5 H 5 ) with dithioacetic acid, CH 3 CS 2 H, leads to loss of the cycloheptatrienyl to give (η 5 -C 5 H 5 )Ti(S 2 CCH 3 ) 3 . 219 and Cp(η 8 SiC≡CSiMe 3 ] revealed that BTMSA serves as a four-electron ligand to two equivalent (η 8 -C 8 H 8 )Ti units. The average C-C distance of 1.51Å in the acetylene ligand is close to that of a sp 3 carbon -carbon single bond, however, the high thermal stability and a large down-field chemical shift of the acetylenic carbon atoms (δ292.8 ppm) suggests unusually high π -back-bonding in the Ti -acetylene bond.…”
Section: Cyclopentadienyl-cycloheptatri Enyl Complexesmentioning
confidence: 99%